1984
DOI: 10.1055/s-2007-1017421
|View full text |Cite
|
Sign up to set email alerts
|

A Placebo-controlled Study of the Antidepressant Activity of Moclobemide,A New MAO-A Inhibitor

Abstract: Preliminary open trials performed by the authors and others with Moclobemide, a new MAO-A inhibitor, indicated that the drug has a satisfactory antidepressant activity. In the present double-blind study Moclobemide has been compared to placebo in a group of 34 unipolar psychotic or neurotic depressed patients. The mean daily dose of Moclobemide was 297 mg and treatment lasted from two to four weeks. Drug effectiveness was measured by improvements in the Hamilton Rating Scale for Depression (HRSD), Clinical Glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…Clinical studies have shown that moclobemide is superior to placebo (Casacchia et al, 1984) and is as effective as clomipramine (Larsen et al, 1984) and amitriptyline (Norman et al, 1985) in treating depressive patients. This indicates that the MAO inhibiting effect of moclobemide is sufficient to elicit clinical improvement at a dose used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have shown that moclobemide is superior to placebo (Casacchia et al, 1984) and is as effective as clomipramine (Larsen et al, 1984) and amitriptyline (Norman et al, 1985) in treating depressive patients. This indicates that the MAO inhibiting effect of moclobemide is sufficient to elicit clinical improvement at a dose used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Moclobemide is a new, reversible (Waldmeier, 1985) MAO-A selective (Koulu et al, 1989;Wiesel et al, 1985) MAOI with few adverse effects and clear antidepressant properties (Casacchia et al, 1984;Dajas et al, 1984;Larsen et al, 1984;Stabl et al, 1989). Moclobemide penetrates well the brain, maximal concentrations of moclobemide in CSF are reached 2 h after oral administration and high CSF/plasma ratio (0.5) can be obtained (Lauy et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical phase III trials have shown that the drug possesses clear antidepressant therapeutic efficacy comparable with that of some classical tricyclic drugs (Larsen et al, 1984;Casacchia et al, 1984;Norman et al, 1985;Lensch et al, 1987). Compared with older irreversible and non-selective MAO inhibitors, the tyramine-potentiating effect of moclobemide is relatively slight (Korn et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Subgroup analyses found no difference in efficacy between moclobemide and imipramine in patients with endogenous depression (ICD-9). Furthermore, three smaller studies revealed no difference in the antidepressant activity of the two drugs (41,127,199).…”
Section: Imipraminementioning
confidence: 98%